THEORETICAL PRINCIPLES OF FUTURE ENGLISH TEACHERS PROFESSIONAL TRAINING BY MEANS OF DISTANCE LEARNING IN POLAND HIGHER EDUCATION INSTITUTIONS - Алла Штепура (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2021)
The article analyzes the theoretical foundations of professional training of future English teachers by means of distance learning in higher educational institutions of the Republic of Poland. The use of distance learning tools in the training of future English teachers, psychological aspects of distance learning, changing the role of the teacher, the theory of multilateral education are the subject of active research by scientists. The research of Polish scholars highlights the methodological and didactic features of the training of future English teachers by means of distance learning. The importance of innovative forms and methods in the training of future foreign language teachers is revealed. The need for constant monitoring of the learning environment in the lifelong learning process is emphasized. It is noted that the global informatization of society and the rapid development of information and communication technologies place new demands on edu-cation. The directions of research singled out by Polish and Ukrainian scientists in the process of informatization of education are generalized. The expansion of international relations and the growing interest in learning foreign languages as a means of communication encourages European countries, in particular the Republic of Poland, to reform and improve the special professional training of English teachers in both traditional and alternative forms of education. The works analyzed in the bibliographic analysis are an important source of information for a com-parative analysis of the training of future English teachers in distance learning in order to justify ways to use constructive ideas of the Polish experience of distance learning in higher education in Ukraine